2021
DOI: 10.21203/rs.3.rs-114156/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Primate Speciation Links to Massive and Directional Shrinkage of the Dinucleotide Short Tandem Repeat Compartment.

Abstract: The evolutionary trend of short tandem repeats (STRs) at the crossroads of speciation remains largely elusive and attributed to random evolution for the most part. Here we investigated the dinucleotide STR compartment in primate speciation. We selected six species, which shared sequential chronological ancestors, including mouse, macaque, gorilla, chimpanzee, bonobo, and human, and collected three sets of data on the abundance of all classes of dinucleotide STRs (≥6-repeats) for three regions of every chrom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 28 publications
(28 reference statements)
1
1
0
Order By: Relevance
“…The AT-TTU colonies were signi cantly larger and more complex than the CG-rich colonies that we reported previously [20,21]. These ndings support a more signi cant role of AT-rich sequences in comparison with CG-rich sequences, as crossover and recombination hotspots.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…The AT-TTU colonies were signi cantly larger and more complex than the CG-rich colonies that we reported previously [20,21]. These ndings support a more signi cant role of AT-rich sequences in comparison with CG-rich sequences, as crossover and recombination hotspots.…”
Section: Discussionsupporting
confidence: 80%
“…We previously reported that CG-rich trinucleotide two-repeat units (CG-TTUs) form colonies of exceeding signi cance across the human genome, based on Poisson distribution [20,21]. Several of the large and medium size colonies that were further analyzed in other species, unveiled crossover and recombination hotspots, shared across primates, and in some instances, even in mouse.…”
Section: Introductionmentioning
confidence: 99%